2013
DOI: 10.1016/j.bbi.2012.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Higher susceptibility to experimental autoimmune encephalomyelitis in Muc1-deficient mice is associated with increased Th1/Th17 responses

Abstract: Multiple sclerosis (MS) is an autoimmune disease of the central nervous system in which dendritic cells (DC) play an important role in the development of inflammatory responses. Recently it has been shown that Muc1, a membrane tethered glycoprotein, has an ability to suppress inflammatory responses in cultured DC. The objective of this study was to investigate the possible involvement of Muc1 in the development of MS using experimental encephalomyelitis (EAE) in mice, a widely used animal model of MS. Our resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 39 publications
1
15
0
Order By: Relevance
“…Studies from various research groups, using wild-type (WT) and Muc1 −/− knockout mice, have shown MUC1 to be associated with an anti-inflammatory/immune-regulatory effect, analogous to other co-inhibitory molecules ( 70 72 ).…”
Section: Experimental Evidence Supporting the Role Of Muc1 As An Immumentioning
confidence: 99%
See 2 more Smart Citations
“…Studies from various research groups, using wild-type (WT) and Muc1 −/− knockout mice, have shown MUC1 to be associated with an anti-inflammatory/immune-regulatory effect, analogous to other co-inhibitory molecules ( 70 72 ).…”
Section: Experimental Evidence Supporting the Role Of Muc1 As An Immumentioning
confidence: 99%
“…Muc1 −/− mice were shown to develop greater experimental autoimmune encephalomyelitis (EAE) symptoms compared to wild-type (WT) mice, with increased numbers of Th1 and Th17 cells infiltrating into the CNS. It was shown that splenocytes from Muc1 −/− KO mice had greater amounts of IL-1β, IL-6, and IL-12 but lesser amounts of IL-10 production, compared to wild-type mice ( 72 ). It was also shown that splenocytes from Muc1 −/− KO mice, which were stimulated with anti-CD3 or anti-CD3 and anti-CD28, expressed higher levels of T-bet, ROR-γ and cytokines IFN-γ and IL-17, compared to WT mice.…”
Section: Experimental Evidence Supporting the Role Of Muc1 As An Immumentioning
confidence: 99%
See 1 more Smart Citation
“…16 In addition, production of the antiinflammatory IL-10 and type I interferon (IFN) has been shown to correlate with increased MUC1 expression. [17][18][19] Investigations in mice with Helicobacter pylori-induced gastritis revealed that Muc1 expression negatively regulates the NLRP3 inflammasome, which mediates production of IL-1b. 20 Taken together, these data suggest that in addition to a barrier role to infection, MUC1 may also be involved with regulation of inflammation in response to infection.…”
Section: Introductionmentioning
confidence: 99%
“… Barrera et al found that TNF tended to increase the mRNA expression of MUC1 gene by mucin–cytokine signaling loop in inflammation environment. Interestingly, the anti‐inflammatory properties are observed in knockout mice of MUC1 gene . In patients with T2DM, low‐grade inflammation has been regarded to be a common characteristic; therefore, inflammation may increase the MUC1 gene expression in various kinds of cells in patients with T2DM.…”
Section: Discussionmentioning
confidence: 75%